Ultrahigh concentration exfoliation and aqueous dispersion of few-layer graphene by excluded volume effect - Zhiyuan Xiong; Luyan Shen; Jin Long; Xiao Li; Ke Zhou; Gyeong Min Choi; Kangtai Ou; GuiYan Yang; Weichun Ma; Heon Sang Lee; Youyi Sun; Dan Li (Nature Communications)
Abstract Colloidal properties of nanoparticles are intricately linked to their morphology. Traditionally, achieving high-concentration dispersions of two-dimensional (2D) nanosheets has proven challenging as they tend to agglomerate or re-stack under increased surface contact and Van der Waals attraction. Here, we unveil an excluded volume effect enabled by 2D morphology, which can be coupled with electrostatic repulsion to synthesize high-concentration aqueous graphene dispersions. To achieve this, we designed a sequential process involving edge oxidation, bubble expansion and mechanical shearing, through which graphite flakes were exfoliated into aqueous dispersions with ~94.5 wt.% yield of few-layer graphene, high concentration exceeding 100 mg mL-1, long-term stability over ~550 days, and large-scale wet processability. Structural analysis and theoretical modeling suggested that the 2D morphology of the resultant graphene nanosheets facilitates inter-sheet repulsive excluded volume interactions, leading to a fractal jammed network structure composed of nanosheets and tactoids to prevent their agglomeration. This effect was further leveraged in a continuous stirred tank reactor for the pilot-scale production of concentrated graphene dispersions. Our study unveils the role of excluded volume effect in stabilizing 2D-material colloids for industrial production and processing.